Transformation Dynamics of Societies in Old Industrial Cities from A Global Comparative Perspective - Osman, Taher (Journal of Social Transformation and Regional Development, 2022)
The decline of societies in old industrial cities is evident in numerous cases in developed countries. Cities that once functioned as dominant industrial centers have faced severe population loss and subsequent social and environmental challenges during the process of economic restructuring. This study aims to identify the common patterns of industrial transition and demographic changes at the city level to determine the factors of growth and decline of industrial cities from a global comparative perspective. Statistical data on industry and population from 1950 to 2010 in the US, Japan, and Korea are collected at the city level. Cities are classified according to industrial characteristics (dominance, type, and composition of industries) and demographic change patterns (continued increase, peak, recent decline, continued decline, slowdown, recovery, and steady); a comparative analysis is conducted in each classified group. The results of the study suggest relevant issues between Japan and Korea industrial cities to prepare strategies for imminent industrial transition and management of urban areas with the cooperation of local stakeholders. This should enable past and present industrial cities to achieve sustainable development for future transformation.